2017
DOI: 10.3390/atmos8010019
|View full text |Cite
|
Sign up to set email alerts
|

Tracheobronchial and Alveolar Particle Surface Area Doses in Smokers

Abstract: Cigarette smoke is the main cause of lung cancer events. Mainstream cigarette smoke (MSS) is a direct concern for smokers, but also the secondhand smoke (SHS) contributes to the smoker exposure. In addition, smoker exposure is affected by the "free-smoke" particle exposure (B), related to the micro-environments where smokers spend time. The aim of this paper is to evaluate the daily alveolar and tracheobronchial deposited fractions of airborne particles for smokers as the sum of these three contributions: MSS,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…Lung dose assessment can help to verify the effective dose relating to possible subclinical and clinical adverse health effects [34]. In this study, the dose of UFPs in terms of surface area deposition in the alveolar tract is greater by one order of magnitude compared to the dose values measured in Italian children living in urban or rural areas [66] and below the total daily deposited dose for typical Italian smokers [67].…”
Section: Discussionmentioning
confidence: 78%
“…Lung dose assessment can help to verify the effective dose relating to possible subclinical and clinical adverse health effects [34]. In this study, the dose of UFPs in terms of surface area deposition in the alveolar tract is greater by one order of magnitude compared to the dose values measured in Italian children living in urban or rural areas [66] and below the total daily deposited dose for typical Italian smokers [67].…”
Section: Discussionmentioning
confidence: 78%
“…Daily mean DSA doses in the intrathoracic airways were estimated to be 141.6 ± 206.2 cm 2 /day, based on the kitchen PSD and personal exposure concentrations. A study on cigarette smoke particles (CSP) conducted in Italy, estimated the intrathoracic particle surface area dose from mainstream cigarette smoke to be 885 cm 2 /day for typical adult female smokers 46 . This study reported an average of 11.8 cigarettes per day for female smokers, with an average 11.5 puffs per cigarette and a puff time of 1.8s, resulting in a total puff time of approximately 4 minutes per day.…”
Section: Discussionmentioning
confidence: 99%
“…measuring the exposure to airborne particle concentrations at a personal scale by means of handheld particle counters (Pacitto et al, 2018;Pacitto et al, 2020;Wallace & Ott, 2011). The study was limited to the non-smoking population and non-industrial working environments; the smoking population should be analyzed separately due to the large dose they typically receive, as should people working in industrial jobs characterized by specific particle sources (Fuoco et al, 2017). Thus, the volunteers considered in this study, to characterize the different environments in terms of submicron particle concentrations, were all adults (both male and female), office workers, and nonsmokers.…”
Section: Methodsmentioning
confidence: 99%